Enhancing Secondary School Students' Mathematical Literacy through Wordwall-assisted Connecting, Organizing, Reflecting, Extending Model - Fisher, Dahlia; Al-Tamar, Jasem (Program Magister Pendidikan Matematika, Pascasarjana, Universitas Pasundan in collaboration with Asosiasi Guru Matematika Indonesia (AGMI) and Indonesian Mathematics Educators' Society (IMES), 2024)
Mathematical literacy helps to understand problems and develop mathematical knowledge to solve various complex problems. However, based on research conducted by the OECD through PISA in 2022, the mathematical literacy skills of Indonesian students are still far below the international average. Purpose of this study was to determine the mathematical literacy abilities of students who received the Connecting, Organizing, Reflecting, Extending (CORE) model with the help of Wordwall compared to students who received conventional learning models. The method used in this research is a quasi-Class with CORE model assisted by Wordwallal method with a nonequivalent Class with Expository modelgroup design. The subjects in this study were eight grader students of SMPN 40 Bandung, the research samples divided into two groups, VIII A as the Class with Expository modelgroup and VIII B as the Class with CORE model assisted by Wordwallal group. Samples taken by purposive technique. In this study, data taken by test of students' mathematical literacy skills conducted before the learning and after the learning treatment. The data obtained were then processed by carrying out a mean difference test with the help of IBM SPSS Statistics 26.0 for Windows. Based on the results of the study, it can be concluded that the mathematical literacy abilities of students who received the Wordwall-assisted CORE model were higher than the mathematical literacy abilities of students who received Expository model.